KERAGAAN VARIETAS UNGGUL BARU PADI SAWAH DENGAN SISTEM TANAM JAJAR LEGOWO 4:1 DI DESA GRENGGENG KECAMATAN KARANGANYAR KABUPATEN KEBUMEN - Diah Budiati; Umi Barokah (Jurnal Agroteknologi (Agronu), 2022)
The cropping system in rice cultivation is very influential on the components of cultivation and crop production. This influence occurs in light capture for photosynthesis, plant water requirements, nutrient absorption by roots, space availability which determines weed competition with plants, and microclimate under the canopy which affects the development of pests and plant diseases. The jajar legowo planting system gave better yields on the number of tillers, weight of grain per tonne and index of increasing the number of leaves. Another obstacle in Grenggeng Village, Karanganyar District, is the lack of information about new superior varieties of rice and the jajar legowo planting system to farmers so that farmers still plant Ciherang and IR64. For these problems, a solution is needed so that the rice production of farmers in Grenggeng Village, Karanganyar District can increase, namely by introducing new high-yielding varieties of rice by testing the performance of new high-yielding varieties of rice and planting with the jajar legowo planting system. The research was carried out in Grenggeng Village, Karanganyar District, Kebumen Regency from October 2020 to March 2021. A total of seven new high yielding varieties of lowland rice and three farmers' favorite comparison varieties, namely Ciherang, Mekongga, and IR64 were tested in this study. Planting was carried out by transplanting using 25 Days After Sowing (HSS) seeds as much as 1 seed/planting hole with a 4:1 row legowo planting system with a spacing of 25 cm x 12.5 cm x 50 cm on a plot measuring 8 m x 5 m. The study was arranged using a Completely Randomized Block Design with four replications. Keywords: new, rice, system, variety